Therapeutic hypothermia after resuscitated cardiac arrest: benefits in survival and neurological outcome. (14th October 2021) - Olivares Martinez, B; Rivadeneira Ruiz, M; Seoane Garcia, T; Fernandez Valenzuela, M I; Barea Gonzalez, C; Garcia Rubira, J C
Abstract: Introduction: The benefits of therapeutic hypothermia in patients remaining in coma after resuscitated cardiac arrest are still controversial, specially for nonshockable rhythm. This study aims to assess the effects of this technique in survival and neurological outcome in comatous patients after resuscitated cardiac arrest. Methods: Retrospective analysis of patients admitted to a Coronary Care Unit from 2006 to 2020 who remained in coma (Glasgow Coma Scale ≤10) after resuscitated cardiac arrest. We compared intrahospital mortality and neurological outcome at discharge between patients who were treated with therapeutic hypothermia and those who weren't. We used intravascular cooling catheter with a target core temperature of 33°C, which was maintained for 24 hours. We performed a subgroup analysis to compare shockable and nonshockable rhythm. Neurological outcome was evaluated with the Cerebral Performance Categories Scale (CPC), which considers survival without limiting disability (CPC 1–2) as favourable neurological outcome. Results: A total of 272 patients were admitted at our Coronary Care Unit after resuscitated cardiac arrest. 182 patients remained in coma after cardiac arrest. The median age was 65.83±0.98 years and 29.1% were women. 70 patients (38.46%) were treated with therapeutic hypothermia – 44 (62.85%) of them had shockable rhythm at presentation and 26 (37.14%), nonshockable rhythm. When we analysed all patients with shockable rhythm, mortality was significantly lower in those treated with therapeutic hypothermia (25% vs 53.8%, p=0.004). In nonshockable rhythm, there was a tendency for lower mortality in the hypothermia group (73.1% vs. 85%, p=0.19). Regarding neurological outcomes, we observed that therapeutic hypothermia also improved neurological outcome at discharge in patients with initial shockable rhythm (CPC 1–2 in 68.2% vs. 26.9%, p<0.001). On the other hand, more patients with nonshockable rhythm had a CPC 1–2 with this technique, although these results didn't reach statistical significance (19.2% vs. 10%, p=0.24). Conclusions: According to our experience, therapeutic hypothermia in patients who remained in coma after resuscitated cardiac arrest showed favourable results in survival and neurological outcome both in shockable and nonshockable rhythm. FUNDunding Acknowledgement: Type of funding sources: None.